Draft Annual Plan 1983-84 Volume II General Areas Government of Assam - Planning Commission (Planning Commission, 1983)
It is seen from the above that the foodgrains production target has been surpassed and this is the all time high production in the State. In oilseeds also the target has been surpassed and this is also all time high production. Oily in respect of Sugarcane and Jute the targets could not be achieved.
Government of Assam, Planning and Development Department